Assessing corticosteroid utilization and mortality risk in septic shock: insights from network meta-analysis - Sutrisno, Wibowo; Dzhyvak, Volodymyr (Deka in Medicine, 2024)
BACKGROUND: Despite current guidelines recommending corticosteroid administration in septic shock management, there is ongoing controversy regarding their impact on mortality rates and the most effective corticosteroid type. OBJECTIVES: To assess corticosteroid use and mortality risk in septic shock via network meta-analysis. METHODS: A comprehensive network meta-analysis was undertaken by retrieving articles from PubMed, Embase, and Scopus databases. Pertinent data encompassing baseline characteristics of articles, definitions of sepsis, types of corticosteroids employed, and mortality rates were systematically extracted from each article. The Manthel Hanzhel method alongside a network meta-analysis approach was employed to evaluate the influence of corticosteroid administration on mortality risk among individuals diagnosed with septic shock. RESULTS: Our analysis comprised a total of 50 articles. While indirect comparison failed to yield statistically significant results regarding the reduction in mortality risk, direct comparison indicated that corticosteroid administration was linked to a decreased risk of mortality among septic shock individuals (OR: 0.80; 95%CI: 0.68, 0.93; p Egger: 0.0550; p Heterogeneity: 0.0010; p: 0.0040). Furthermore, among all the types of corticosteroids analyzed, only the hydrocortisone and fludrocortisone combination demonstrated an association with reduced mortality risk in septic shock patients. Individuals receiving this combination therapy exhibited decreased likelihood of mortality compared to those receiving a placebo (OR: 0.78; 95%CI: 0.64, 0.96; p Egger: 0.3082; p Heterogeneity: 0.8570; p: 0.0190). CONCLUSION: Our study emphasizes the significance of corticosteroid therapy, particularly highlighting the hydrocortisone and fludrocortisone combination, for septic shock management.